Chempaka: A Flora Motif as Design Identity in Batik Chempaka, PPDK Merbok - Jamaludin, Juaini; Yusoff, Zaidi; Mohd Yusof, Fadila; Abdul Karim, Izza Syahida; Sa’ad, Sharina (Idealogy Journal, 2023)
Batik Malaysia refers to the traditional Malaysian art of batik-making which includes the application of wax and dyes to cloth to produce elaborate patterns and design. Batik has a long history in Malaysia and is a key part of the country’s cultural legacy, representing its identity and customs. This paper discusses the floral motif as design identity and production of the Chempaka flower motif. It explores the history and cultural significance of the Chempaka flower motif in batik making and how it has been adapted to create modern design. Overall, the paper concludes with the importance of the Cempaka flower motif as a design identity and the need to preserve its cultural significance in the batik industry. Keywords: Batik design, Batik industry, Batik motif, Batik identity.